Autoantibodies against TIF‐1‐γ and CADM‐140 in Spanish patients with clinically amyopathic dermatomyositis (CADM): clinical significance and diagnostic utility. (28th July 2014) - Cuesta‐Mateos, C.; Colom‐Fernández, B.; Portero‐Sainz, I.; Tejedor, R.; García‐García, C.; Concha‐Garzón, M.J.; De las Heras‐Alonso, M.E.; Martínez, M.A.; Juarez, C.; Muñoz‐Calleja, C.
Abstract Background Patients with clinically amyopathic dermatomyositis (CADM) appear to be at risk for developing cancer and interstitial lung diseases, but population data to confirm this hypothesis are limited. Moreover, CADM presents cutaneous and histological findings that may overlap with subacute cutaneous lupus erythematosus (SCLE). Objectives To determine the association between myositis‐specific autoantibodies, myositis‐associated autoantibodies and CADM in Spanish patients. In addition, to study the usefulness of these autoantibodies in the differential diagnosis between CADM and SCLE. Methods Serum samples were tested for myositis‐specific autoantibodies and myositis‐associated autoantibodies through immunoprecipitation and other standardized methods. Results Anti‐CADM‐p140 and anti‐p155 antibodies were the only myositis‐specific autoantibodies found and were associated with interstitial lung diseases and cancer respectively. No myositis‐associated autoantibodies were found in CADM. Moreover, clinical subsets and proportions seemed to differ from Asian cohorts, where anti‐CADM‐p140 is considered a CADM hallmark antibody and a risk factor for the development of interstitial lung disease. Interestingly, anti‐SSA was highly associated with SCLE, whereas no myositis‐specific autoantibodies were found in this entity. Limitations of the study Association between CADM and myositis‐specific autoantibodies and differences between CADM and SCLE were tested on a relatively small cohort of patients. Conclusion There is an association between cancer‐associated myositis and interstitial lung diseases and their hallmark autoantibodies in our cohort. In addition, the combined determination of myositis‐specific autoantibodies and SSA autoantibodies may help to accurately discriminate SCLE from CADM.